어머니의 구강보건관리행태와 자녀의 우식경험유치지수와의 관련성 - 장경애; 김동열 (Han'guk Ch'iwisaeng Hakhoe chi, 2010)
Objectives: This study was to assess the children's mean number of decayed or filled primary teeth in relation to their mother's oral health behavior and then to increase children's oral health. Methods: The 346 children and their mothers were selected for this study. The children were 4 or 7 years old in the 4 dental clinics in Busan and Kyungnam, Korea. Data were collected by examination on children and self-administrated questionnaire on their mothers. The questionnaire was surveyed mother's oral health behaviour and children experienced dental caries or not and the number of decayed or filled they had were used as outcome variables. Results: 1. The mother's education level affected children's dft index significantly(p<0.05), In the case of tooth brushing method of children, the group with circle teeth wipes shows the low dft index (p<0.01). 2. On the other hand the group with snack as food eaten between meals has high dft index(p<0.001). 3. The group with mother's visiting to dentist within recent 1 year, experience in removing plaque or willing to attend the oral health education show low dft index(p<0.05). The important variables affecting to dft index are experience with oral health education, tooth brushing guidance, replacement of toothbrushes, the kind of food eaten between meals, recent experience of plaque removal and willing to participating in the oral health class. Conclusions: This study showed that the mother's oral health behavior and concern play an important role for the prevention of preschooler's dental caries. Dental health education would be focused on the mothers, expecially for the practice of preventive behavior by preschools themselves. KCI Citation Count: 7